Didactics of Motor Activity in Sensory and Intellectual Disability - Mattia Caterina Maietta; Francesco Tafuri (Pensa MultiMedia, 2022)
The purpose of this work is to propose a working suggestion for all professional, that, within the school, meet people with sensory and intellectual disabilities on a daily basis. First, the characteristics of the different disabilities are illustrated, then the adapted activities are described. Activities adapted are, by definition inclusive, promote optimal living conditions and a good system of relationships. Through sport, in fact, people with disabilities could feel part of the community and its network of relationships. Nowadays everyone can practice sports, having the opportunity to try their hand in various disciplines. Sport is an important educational tool that, through targeted actions, becomes fundamental for emancipation and growth. This work was born out of the need to help children with intellectual and sensory disabilities in everyday life, through motor activity, setting as objectives the improvement of motor skills, attention, concentration, and of the basic motor schemes, the psychic, intellectual and sensory conditions, the strengthening of relationships with others, in particular with peers, the development of self-discovery and confidence in one's own abilities and autonomy in daily activities.